Pemanfaatan Media Sosial Di Tengah Pandemi Covid-19 Di Kalangan Penyuluh Pertanian dan Perikanan Kota Depok - Moh Zaenal Abidin Eko Putro; Achmad Bakhrul Muchtasib (Jurnalistik dan Media, 2023)
During the implementation of learning from home at all levels of education due to pandemic covid 19 which began in March 2020, the utilization of social media platforms as well as meeting apps was mushrooming. The digitalization of communication not only happened in the academic realm but also in other professions including the agriculture and fishery instruction realm. This article aims to elaborate on what extent to the utilization of social media platforms among agriculture and fishery instruction in Depok of West Java. Based on a qualitative research method which lies primarily on the following data gathering techniques, namely interview, literature study, and observation, this article shows that the utilization of social media platforms for information exchange among agriculture and fishery instructors was very low. People who want to consult prefer face-to-face communication to online communication through social media platforms. Keywords: pandemic covid 19, social media, agriculture and fishery instructors, sending information